Pengaruh Literasi Keuangan, Efek Teman Sebaya, dan Sumber Informasi terhadap Perilaku Siswa dalam Penggunaan Aplikasi Fintech - Alamsjah; Soraya, Zalkha; Aisyah, Siti; Dwiyanti, Friska; Sultan, Annisa (Politeknik Ganesha Medan, 2024)
This study aims to determine whether financial literacy, peer effects, and sources of information influence the behavior of students at Muhammadiyah 7 Makassar High School in using fintech. The research employs a quantitative approach to examine specific populations or samples with the goal of testing established hypotheses. The findings reveal that financial literacy does not have a significant impact on fintech usage behavior. Conversely, peer effects and sources of information have a significant impact on fintech usage behavior. The urgency of this research lies in the importance of understanding the factors that influence the adoption of financial technology among students, who are the future generation and potential users of fintech. By identifying key factors that affect their behavior, schools and policymakers can design more effective educational programs and interventions to enhance understanding and responsible use of fintech. Overall, financial literacy, peer effects, and sources of information collectively account for 71.9% of the influence on fintech usage behavior, while the remaining 29.1% is affected by other variables not discussed in this study.